Annexin A12–26 Treatment Improves Skin Heterologous Transplantation by Modulating Inflammation and Angiogenesis Processes - Lacerda, Jéssica Zani; Drewes, Carine Cristiane; Mimura, Kallyne Kioko Oliveira; Zanon, Caroline de Freitas; Ansari, Tahera; Gil, Cristiane Damas; Greco, Karin Vicente; Farsky, Sandra Helena Poliselli; Oliani, Sonia Maria (Frontiers in Pharmacology, 2018)
Skin graft successful depends on reduction of local inflammation evoked by the surgical lesion and efficient neovascularization to nutrition the graft. It has been shown that N-terminal portion of the Annexin A1 protein (AnxA1) with its anti-inflammatory properties induces epithelial mucosa repair and presents potential therapeutic approaches. The role of AnxA1 on wound healing has not been explored and we investigated in this study the effect of the peptide Ac2-26 (N-terminal AnxA1 peptide Ac2-26; AnxA12-26) on heterologous skin scaffolds transplantation in BALB/c mice, focusing on inflammation and angiogenesis. Treatment with AnxA12-26, once a day, from day 3-60 after scaffold implantation improved the take of the implant, induced vessels formation, enhanced gene and protein levels of the vascular growth factor-A (VEGF-A) and fibroblast influx into allograft tissue. It also decreased pro- while increasing anti-inflammatory cytokines. The pro-angiogenic activity of AnxA12-26 was corroborated by topical application of AnxA12-26 on the subcutaneous tissue of mice. Moreover, treatment of human umbilical endothelial cells (HUVEC) with AnxA12-26 improved proliferation, shortened cycle, increased migration and actin polymerization similarly to those evoked by VEGF-A. The peptide treatment instead only potentiated the tube formation induced by VEGF-A. Collectively, our data showed that AnxA12-26 treatment favours the tissue regeneration after skin grafting by avoiding exacerbated inflammation and improving the angiogenesis process.